Malaysia Economic Monitor, June 2018 : Navigating Change - World Bank Group (World Bank, Washington, DC, 2018)
The historic outcome of Malaysia's recent elections provides an unprecedented opportunity for change. The country's 14th General Elections which took place on May 9, 2018, in the context of widespread citizen concern regarding the degree to which the proceeds of economic growth have been shared across the Malaysian society and a call for increased government accountability, have resulted in the nation's first change in government since its independence in 1957. The new government's emerging economic policy framework is strongly guided by its election manifesto Buku Harapan, which responds to these popular sentiments. Heightened uncertainty amid the political transition exacerbated the ongoing turbulence in the financial markets arising from external factors. In the period between the elections and end-May, Malaysia's 5- and 10-year sovereign spreads against US Treasuries increased by 24 and 27 basis points respectively, while the stock market fell by three percent. Meanwhile, RM19 billion of foreign capital was withdrawn from the domestic financial markets in May as post-election market turbulence coincided with heightened investor uncertainty about the emerging markets asset class. However, since then volatility in the financial markets has been largely driven by external factors amid increased global trade tensions, as the uncertainty surrounding the political transition has gradually reduced.